Recent Books Delineating the Emergent Academic Filed of the Study of Information - Gordana Dodig-Crnkovic; Mark Burgin (Proceedings)
One of the imperative tasks of theoretical information studies is exploration of methods and techniques of presentation of information. In this article, we study the presentation of information in the following three books describing the results of the collaboration of researchers with the goal of defining the emergent filed of the Study of Information: Philosophy and Methodology of Information: The Study of Information in a Transdisciplinary Perspective (2019), Theoretical Information Studies: Information in the World (2020) and Information and Computation (2011), published by World Scientific Publishing Co. Series in Information Studies.